Perbedaan Rasio Rentang Lengan-Tinggi Badan pada Mahasiswa Laki-laki dan Perempuan FK Universitas Sebelas Maret - Annisa Budiastuti; Selfi Handayani; Hardjono . (Nexus Biomedika, 2012)
Background: Height is an important clinical indicator to derive Body Mass Index (BMI) and also to estimate Basal Metabolic Rate (BMR). However, height measurement in someone who cannot stand properly like the elderly or lower ekstremity abnormality may become difficult. Therefore, estimating height with another antropometric measurement may become a solution. In another study, arm span showed the highest correlation with standing height. The different morfologic between male and female also important to find the different estimating height formula. Objectives: This research aimed to know arm span to height ratio data in students from Medicine Faculty 2008 of Sebelas Maret University and the differences of arm span to height ratio between male and female. Methods: This research was an analytical observational research with cross sectional approach. The sample data collected using purposive sampling method within inclusion and exclusion criteria. From the population, 60 samples (30 males and 30 females) chose by simple random sampling method, then measured their height and arm span. Height measured in anatomical position using microtoise staturmeter. Arm span measured using ruler tape from the longest finger in right hand to the longest finger in left hand. All data analyzed using normality test Kolmogorov-Smirnov and followed with t-independent test if the distribution data showed normal. Results : T-independent test result p = 0.03 (p < 0.05). Conclusion: This study found a difference in arm span to height ratio between male and female students in Faculty of Medicine 2008, Sebelas Maret University, Surakarta Keywords: arm span, height, anthropometric measurement, student